ANALYSIS OF JUDGES' DECISIONS REGARDING ISLAMIC INHERITANCE CASES AND ITS IMPLICATIONS FOR FAMILY LAW REFORM IN INDONESIA - Pradikta, Hervin Yoki; Mahmudah, Siti; Susanto, Is (Universitas Islam Negeri Raden Intan Lampung, 2022)
There is a disparity between the decisions of the Religious Courts, the High Religious Courts and the decisions of the Supreme Court related to Islamic inheritance cases since first-instance and appellate-level decisions tend to use normative law, whereas at the cassation level decision has used a progressive legal paradigm. Therefore, this study aims to look at the judge's decision regarding inheritance cases and its implications for legal reform. This research is a qualitative research, a type of library research with the approach of the Legal Pluralism Triangle Concept by Werner Menski. This study uses the theory of legal discovery, maqasyid as-shari'ah, and progressive legal theory, and draws conclusions using inductive thinking. The results of this study indicate that the decisions of the Religious Courts and the High Religious Courts still use a conservative legal paradigm which tends to only serve as mouthpiece for laws, in contrast to the decisions of the Supreme Court which have described the existence of ijtihad by using a progressive or contextual legal paradigm. The implication of the decision on Islamic inheritance for family law reform in Indonesia is that the Supreme Court's decision can be used as jurisprudence andas a reference for realizing the unification of Islamic inheritance law in Indonesia today.